Rapid adaptation of a complex trait during experimental evolution of Mycobacterium tuberculosis - Smith, Tracy M; Youngblom, Madison A; Kernien, John F; Mohamed, Mohamed A; Fry, Sydney S; Bohr, Lindsey L; Mortimer, Tatum D; O'Neill, Mary B; Pepperell, Caitlin S (eLife, 2022)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (M. tb), is a leading cause of death due to infectious disease. TB is not traditionally associated with biofilms, but M. tb biofilms are linked with drug and immune tolerance and there is increasing recognition of their contribution to the recalcitrance of TB infections. Here, we used M. tb experimental evolution to investigate this complex phenotype and identify candidate loci controlling biofilm formation. We identified novel candidate loci, adding to our understanding of the genetic architecture underlying M. tb biofilm development. Under selective pressure to grow as a biofilm, regulatory mutations rapidly swept to fixation and were associated with changes in multiple traits, including extracellular matrix production, cell size, and growth rate. Genetic and phenotypic paths to enhanced biofilm growth varied according to the genetic background of the parent strain, suggesting that epistatic interactions are important in M. tb adaptation to changing environments.
Keywords: Mycobacterium tuberculosis; biofilms; experimental evolution; population genetics